28 Do the risks and benefits of thoracoscopic af ablation justify its endorsement in guidelines? a propensity matched study with catheter ablation. (June 2018) - Pearman, Charles; Redfern, James; Williams, Emmanuel; Modi, Simon; Shaw, Mathew; King, Rebecca; Hall, Mark; Waktare, Johan; Mahida, Saagar; Todd, Derick; Snowdon, Richard; Mediratta, Neeraj; et al.
Abstract : Introduction: The safety and efficacy of Standalone video assisted thoracoscopic surgical (VATS) ablation for atrial fibrillation (AF) has not been established. In particular, comparative data with catheter ablation (CA) are scarce. Methods: We prospectively collected data on 30 consecutive VATS AF ablations (mean age 58±10 years, 26 male) performed by an a single surgeon, the first 20 of which were proctored by external surgeons. We compared peri-procedural complications and medium-term arrhythmia free survival to those of 90 propensity-matched patients who underwent RF CA during the same time period. Results: VATS and catheter patients were well matched with regard to all measured demographics (table 1). 6 (20.0%) patients undergoing VATS experienced 1 major complication (death n=1, stroke n=2, conversion to sternotomy n=3, phrenic nerve injury n=2). This was significantly higher than the 1 (1.1%) major complication rate (tamponade requiring drainage) seen with CA; p<0.001. The median hospital stay with VATS (7 days) was significantly greater than with CA (2 days), p<0.001. Over the follow up period, 12 (42.9%) and 5 (17.9%) patients in the VATS group and 16 (18.6%) and 13 (15.1%) patients in the CA group needed electrical cardioversion and repeat CA respectively (p=0.009 and p=0.13 respectively). At a mean follow up of 15.6 months, single procedure pragmatic arrhythmia-free survival was 50% in the VATS and 66% in the CA cohort, p=0.18 (figure 1). Conclusions: Standalone VATS AF ablation is associated with similar success rates to catheter ablation, but with a significantly higher rate of major complications.